2012
DOI: 10.1097/tp.0b013e31825f0f97
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction in Patients With End-Stage Liver Disease is Associated With Development of Heart Failure Early After Liver Transplantation

Abstract: This study suggests that elevated markers of diastolic dysfunction during pre-LTx echocardiographic evaluation are associated with an excess risk of HF and may predict post-LTx survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 26 publications
3
83
1
Order By: Relevance
“…In fact, studies which have used clinical and radiological, but not solely echocardiographic, criteria to diagnose post-OLT HF report an incidence threefold higher than ours. 7,8 However, with the large fluid shifts and systemic inflammation seen with OLT, the effects of In the absence of acute ischemia or apparent stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, studies which have used clinical and radiological, but not solely echocardiographic, criteria to diagnose post-OLT HF report an incidence threefold higher than ours. 7,8 However, with the large fluid shifts and systemic inflammation seen with OLT, the effects of In the absence of acute ischemia or apparent stress.…”
Section: Discussionmentioning
confidence: 99%
“…They report incidences ranging from 7% to 27%, depending on the definition of HF and its time of occurrence. [6][7][8] Systolic HF after OLT is a poorly understood entity and may potentially result from a multitude of etiologies. There is paucity of knowledge on predictors of systolic HF occurring soon after OLT, the clinical course of these patients, and prospect for recovery of systolic function.…”
Section: Introductionmentioning
confidence: 99%
“…Some echocardiographic indices of preorthotopic liver transplantation (OLT) DD have been associated with post-OLT heart failure. 4,5 An e/a <1 is known to be an independent predictor of mortality after placement of transjugular intrahepatic | 987 portosystemic shunt. 6 Also some studies have found an association between DD and post-OLT mortality while others have found no association.…”
Section: Introductionmentioning
confidence: 99%
“…6 Also some studies have found an association between DD and post-OLT mortality while others have found no association. 4,[7][8][9] However, most of these investigations have defined DD based on only one or two echocardiographic parameters, likely adding error to estimation of DD. For instance, e/a is load-dependent parameter, and thus by itself a poor indicator of the grade of DD.…”
Section: Introductionmentioning
confidence: 99%
“…Josefsson et al [25] found it to be associated with a longer ITU stay (14.5 d vs 4 d), a longer inpatient stay (33 d vs 21 d), a higher peri-transplant infection rate (42% vs 19.9%) and higher long term patient and graft mortalities (Figure 10). In a search to identify predictors of heart failure after liver transplantation, Dowsley et al [92] found that markers of diastolic dysfunction on preoperative TTE (E/e' > 10 and LA volume index ≥ 40 mL/m 2 ) were associated with a 3.4 fold and 2.9 fold increase in risk respectively. Furthermore, Kaplan-Meier analysis of LA volume index below and above 40 mL/m 2 revealed survival differences of 82% vs 54% at 1 year and 71% vs 50% at 5 years respectively.…”
Section: Post Operative Coursementioning
confidence: 99%